THE EFFECT OF WORK FACILITIES ON 54.661.11 SPBU WLINGI DISTRICT BLITAR REGENCY - Yoga Dwi Rusdian Putra; Suprianto Suprianto (JOSAR (Journal of Students Academic Research), 2020)
The purpose of this study was to determine the level of work facilities and the level of the employees productivity of 54.661.11 SPBU Wlingi District Blitar Regency, and to determine the effect of work facilities of Employee productivity on the 54661.11 SPBU Wlingi Blitar. The method used is a quantitative approach research method. The subjects of the research were the employees of 54.661.11 SPBU Wlingi Blitar Regency. The research sample uses random sampling techniques. The total number of research 19 village officials (respondents). The data collection methods used in this study are questionnaires that must be filled out by respondents. The analysis technique used is the Product Moment analysis technique from Karl Person. The results of the validity test of each scale of work facilities and productivity of village officials received amounted to 15 items and 10 items. The result of this research is a significant influence of work facilities to the employees productivity of 54.661.11 SPBU known ˃ , = 0.536 ˃ 0, 433 then Ho is rejected and Ha is accepted. It means that there is an influence between work facilities to the employees productivity of 54.661.11 SPBU Wlingi Blitar. The coefficient of determination above is or 30%. It means that the variance that occurs in the 30% employee productivity variable is determined by the variance that occurs in the work facilities variable. This understanding is often interpreted the influence of work facilities on employee productivity = 30%, and the remaining 70% are other factors including work motivation, work discipline and others.